The creative intermediate phase of architect Mihailo Mika Čanak (1970) - Anđelković, Goran (Arhitektura i urbanizam, 2024)
This research has been focused on the turning point (1970) in design practice and work of architect Mihailo Mika Čanak. After the disappearance Architectural group Belgrade Five (1954–1970), with the death of architect Milosav Mitić, and before the establishment of closer cooperation with the architect Aleksandar Đokić on the design and construction Belgrade housing settlement Kneževac–Kijevo (1971–1984), great changes took place and turning point in Čanak design practice and construction activity. The review of the preserved architect legacy, as the primary research source, recognized Čanak short creative intermdeiate phase between the first modernist (1957–1970) and the second postmodernist period (1970–1993). Its importance was reflected in the first steps of "softening" the purist expression, re-examining values according to the previous creative phase and turning to new design possibilities in the process of searching for recognizable author’s expression. The goal of research is to chronologically structure and systematize three developmental steps between accepted modernist and emerging postmodernist values in Serbian architecture at the end of the seventh and beginning of the eighth decade of the twentieth century: the autonomy newly formed unit, the Center for Housing Study IMS (1970–1973), as a result Čanak effort to improve the position of Institute architects, with a strong turn towards scientific research work and freedom of authorial expression on architectural competitions; a hommage to modernism and industrial aesthetics, a recognizable feature of the architectural group to which he belonged during the fifties and sixties of the twentieth century, in the first independent author’s realization of the residential Block 2 in Novi Sad (1970–1972) and the redefinition of residential space concept; and a radical and avantgarde step toward sophisticated high technology, embodied in slich-tech aesthetics as a transitional solution to postmodernism on architectural competition for Office tower in Sremska Street (1970).